A (New) East–West-Divide? Representative Democracy in Germany 30 Years after Unification. Issue 1 (2nd January 2023) - Reiser, Marion; Reiter, Renate
Abstract : Thirty years after the fall of the Berlin Wall, the public and scientific debate about the state of unification has regained considerable momentum. The debate stresses in particular the persistent, returning, and even deepened East-West differences which refer to central elements and promises of representative democracy. However, it is a controversial and so far unanswered question whether and in which way this poses a challenge to the legitimacy and functioning of representative democracy in Germany. Therefore, this Special Issue focuses on the representative democracy by concentrating on its central dimensions, actors, and institutions (citizens, political parties and parliaments, and elites). The introduction outlines the three key questions which are addressed by the contributors regarding (1) to the status of unification in longitudinal and in cross-sectional perspective, (2) the causes and determinants for ongoing differences and divides between East and West, and (3) the implications for representative democracy in Germany. Moreover, it summarises the results of the contributions and discusses research desiterata for future research on the state of unification and representative democracy in Germany.